2015
DOI: 10.1177/0309364614538090
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of fitting and tuning solid ankle–foot orthoses in early stroke rehabilitation

Abstract: This study provides evidence about the immediate effects of custom solid ankle-foot orthoses on gait of early stroke survivors. Ankle-foot orthosis design specifications are fully described for replication. This study suggests that observing global segment orientation may be more useful than joint angles when fitting and tuning ankle-foot orthoses for optimal ankle-foot orthosis/footwear alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…Franceschini et al [12] showed improvement with use of an AFO in temporospatial parameters including increases in walking speed and cadence combined with decreases in stance time and double support time in patients with chronic hemiplegia. In the study of Carse et al, [13] patients with early stroke had an increase in walking speed, cadence and step length with a solid AFO.…”
Section: Discussionmentioning
confidence: 92%
“…Franceschini et al [12] showed improvement with use of an AFO in temporospatial parameters including increases in walking speed and cadence combined with decreases in stance time and double support time in patients with chronic hemiplegia. In the study of Carse et al, [13] patients with early stroke had an increase in walking speed, cadence and step length with a solid AFO.…”
Section: Discussionmentioning
confidence: 92%
“…Changes in ankle joint position sense, which led to a significant difference in gait velocity and stride length was reported. Carse et al [35] conducted a study on 8 patients who were diagnosed with stroke. In this study, the effect of lower limb re-alignment on gait was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The question wording and choices for the survey were informed by the BPS, 11 Bowers and Ross' paper on the development of the BPS, 9 papers regarding AFO use in post-stroke patients, 4,5,10,[12][13][14][15][22][23][24][25][26] discussion with experts and information from books, and papers regarding designing health care surveys. [17][18][19][20][21][27][28][29][30][31] The wording of the multiple-choice responses to five questions was taken directly from the Screening Tool associated with the BPS to assess participants' understanding and ability to use this Tool.…”
Section: Survey Designmentioning
confidence: 99%
“…Stroke has been a clinical priority for NHS Scotland for over 15 years; in 2017 9,345 people were admitted to Scottish hospitals with a diagnosis of stroke . Mobility problems are a common result of stroke, and improved mobility is a high priority to Scottish stroke patients in their rehabilitation, making effective treatment key to post‐stroke services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation